2022
DOI: 10.1097/md.0000000000031769
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D level in relation to phonetic function among subacute stroke patients

Abstract: There are many stroke patients with decreased phonation ability. Vitamin D is associated with weakness in muscle power and a decreased function of activity and is often accompanied by a deficiency of serum vitamin D in stroke patients. This study was conducted to evaluate the correlation between serum vitamin D level and phonetic function in subacute stroke patients. Among subacute stroke patients, patients with dysphonia were retrospectively recruited. Phonation function was assessed by acoustic analysis usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…5 Voice and associated speech changes in CVA are complex and largely dependent on the location of the cerebral event, especially in subcortical, upper motor neuron, pons, and cerebellar lesions; vocal fold function may also be impaired. 5,13,14 According to one study, vocal fold paresis is reported to occur in approximately 20% of stroke patients. 14,15 Changes in voice quality, similar to other functional impairments caused by the neurological involvement of oropharyngeal muscles, can have a significant impact on the quality of life of stroke patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Voice and associated speech changes in CVA are complex and largely dependent on the location of the cerebral event, especially in subcortical, upper motor neuron, pons, and cerebellar lesions; vocal fold function may also be impaired. 5,13,14 According to one study, vocal fold paresis is reported to occur in approximately 20% of stroke patients. 14,15 Changes in voice quality, similar to other functional impairments caused by the neurological involvement of oropharyngeal muscles, can have a significant impact on the quality of life of stroke patients.…”
mentioning
confidence: 99%
“…5,13,14 According to one study, vocal fold paresis is reported to occur in approximately 20% of stroke patients. 14,15 Changes in voice quality, similar to other functional impairments caused by the neurological involvement of oropharyngeal muscles, can have a significant impact on the quality of life of stroke patients. 16 Objective methods that provide a measurable criterion are used to assess the voice.…”
mentioning
confidence: 99%